Measuring radiotherapy setup errors at multiple neck levels in nasopharyngeal cancer (NPC): A case for differential PTV expansion. Issue 3 (December 2015) - Cheo, Timothy; Loh, Yvonne; Chen, Desiree; Lee, Khai Mun; Tham, Ivan
Abstract: Background and purpose: We aim to quantify the magnitude of the systematic and random setup errors at three different anatomical levels of the neck in Nasopharyngeal Carcinoma (NPC) when clivus matching is used, and recommend appropriate PTV margins for each level. Material and methods: Thirty-six patients undergoing image-guided radiotherapy (IGRT) each with 9 scheduled CBCTs were reviewed. The magnitude of setup errors were measured at the level of the clivus, C4 and C7 vertebrae, before and after CBCT correction. The 3D displacements, systematic and random errors were calculated for each level. The appropriate PTV expansion was determined using Van Herk's formula. Results: Mean 3D displacement was 1.88, 2.66 and 3.35 mm at the clivus, C4 and C7 before correction. The differences were statistically significant ( p < 0.05). The PTV margin required without correction was 2.33, 4.33 and 6.52 mm respectively. These were reduced to 1.20, 3.72 and 6.08 mm after CBCT corrections. Conclusions: Variability is seen in setup errors at the clivus, C4 and C7 vertebral levels. A variable planning margin approach with reduced margin at the clivus is recommended. Use of daily CBCT allows the PTV expansion to be reduced to 1.2 mm.